Prosthetics and assistive technology in ancient Greece and Rome - Draycott, Jane ca. 20./21. Jh (Cambridge University Press, 2023)
This is the first comprehensive study of prosthetics and assistive technology in classical antiquity, integrating literary, documentary, archaeological, and bioarchaeological evidence to provide as full a picture as possible of their importance for the lived experience of people with disabilities in classical antiquity. The volume is not only a work of disability history, but also one of medical, scientific, and technological history, and so will be of interest to members of multiple academic disciplines across multiple historical periods. The chapters cover extremity prostheses, facial prostheses, prosthetic hair, the design, commission and manufacture of prostheses and assistive technology, and the role of care-givers in the lives of ancient people with impairments and disabilities. Lavishly illustrated, the study further contains informative tables that collate the aforementioned different types of evidence in an easily accessible way